DYNAMIC DEVELOPMENT OF THE RESIDENTIAL REAL ESTATE MARKET IN MOSCOW - Yulia A. Milkina; Ekaterina E. Makarova (Наука Красноярья, 2024)
Moscow occupies a special place in the real estate market of the Russian Federation, as it is characterized by a large volume of new residential real estate, the existence of large market players and the presence of high (compared with other regions of the country) effective demand. In many ways, the stability of the Russian real estate market depends on the stability of the Moscow real estate market. For this reason, an analysis of the current state of the Moscow real estate market is of great importance.